Electrostatic Focusing for cavity resonators - Daumenov Т.D.; Khizirova М.А.; Bisarieva, Zh.B. (Recent Contributions to Physics, 2016)
In this paperwork we consider the possibility of using a single lens to modulate the electron beam velocity. It is shown that the use of a single lens as a modulator in speed does not affect the value of the coefficient of interaction with the electron flux field lens. Cavity proposed design can simultaneously perform the role of the electron modulator on the one hand speed and conveying system in the drift space , and the other stream of electrons clots can be focused on the surface of the input window of the output resonator . Cavity resonator with electrostatic focusing improves power klystron type microwave devices by increasing the convection current.